KLS-3021, a multifunctional oncolytic virus, demonstrates potent early-intervention efficacy in preclinical models of prostate-confined and locally advanced prostate cancer - Seo, Jinwon; Park, Kiwon; Lee, Sungmin; Kang, Hyesoo; Kim, Joonsung; Lee, Eunjin; Shin, Jaeil; Hong, Soon-Oh; Kim, Sujeong; Kim, Sun Jin (Frontiers in Oncology, 2026)
IntroductionWith aging male populations, the incidence of prostate cancer is increasing globally. Patients with low- to intermediate-risk disease (Gleason score ≤7) are often managed with close surveillance rather than immediate curative intervention; however, progression in a subset of these individuals narrows the window for effective treatment. Minimally invasive, image-guided local therapy enabling early intervention could prevent disease progression and improve progression-free outcomes. To address this unmet need, we evaluated KLS-3021, a novel oncolytic vaccinia virus encoding PH-20, IL-12, and soluble PD1-Fc.MethodsKLS-3021 was assessed in two orthotopic prostate cancer models: a prostate-confined model with bioluminescence-positive, non-gross tumors, and a visible/palpable locally invasive model with regional lymphatic spread. Mice were randomized to receive vehicle, docetaxel, or KLS-3021, administered on day 9 (prostate-confined) or day 29 (visible/locally invasive) after implantation of luciferase-labeled PC-3 cells. Tumor growth was tracked longitudinally by bioluminescence imaging, and histopathological analyses were conducted at predefined time points.ResultsA single intratumoral injection of KLS-3021 induced profound and durable tumor therapeutic or suppressive efficacy superior to that of docetaxel in prostate-confined or locally invasive diseases. Mechanistic analyses revealed extracellular matrix degradation, enhanced viral spread, increased immune cell infiltration, M1 macrophage polarization, and features of immunogenic cell death in KLS-3021-treated tumors.DiscussionThese results collectively demonstrate the translational potential of KLS-3021 as a minimally invasive or neoadjuvant therapeutic strategy for prostate cancer, especially in patients for whom early, localized intervention is medically feasible.